The Relations of Politics, Law, and Economics in a Social Philosophy Perspective - Abdurrahman, Abdurrahman; Yunus, Nur Rohim; Setiawan, Refly (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
The relationship between politics, law, and economics forms the main foundation in the dynamics of national and social life. These three elements not only influence each other structurally but also create a power structure that directly affects the distribution of social justice, policy-making, and the functioning of state institutions. This study aims to examine in depth how the relationship between politics, law, and economics is formed, implemented, and questioned through a social philosophy approach, and how this approach can open up space for criticism of the structural inequalities that occur. The research method used is qualitative with an interdisciplinary approach that combines political, legal, and economic analysis within a social philosophy framework. Data were obtained through a literature review of critical philosophy, social justice theory, and relevant empirical studies. The analysis was carried out reflectively and thematically on concepts such as power, justice, law as an ideological instrument, and political economy in the context of the state. The results of the study reveal that the relationship between politics, law, and economics is often constructed to maintain the dominance of certain groups, rather than achieving social justice. Law is not always neutral, but usually becomes a tool for legitimising economic and political power. Politics also does not always run within the framework of democratic participation, but is often controlled by market interests. Social philosophy plays a crucial role in dismantling these power structures and providing ethical and critical perspectives to promote policy reform and social stability.Keywords: Social philosophy; political law economy; social justice; power; public policy